TECHNIQUES FOR IMPROVING LISTENING AND SPEAKING SKILLS IN ENGLISH - Ubaydullayev.B.O’,; Maxmudova Madina, (TADQIQOTLAR, 2025)
Abstract This article explores evidence-based and pedagogically grounded techniques for enhancing  English  listening  and  speaking  skills  among  second  language  learners. Drawing on insights from influential works by Brown and Yule (1983), Field (2008), and Richards (2008), as well as from practical teaching resources such as the Active Listening series, Jean Yates’s English Conversation, and digital platforms like Speak English  with  Mr.  Duncan  and  EnglishCentral.com,  the  paper  highlights  how communicative competence can be cultivated through targeted strategies.Key themes include the importance of teaching spoken English as a distinct skill set, the use of authentic listening tasks with real-life conversational input, and the implementation of interactive and task-based speaking activities. Process-oriented listening instruction is emphasized as a means to develop learners’ cognitive listening abilities, while speaking fluency is shown to improve through structured exposure to language chunks, idiomatic expressions,  and  pronunciation  practice.The  paper  also  examines  the  value  of technology-enhanced  resources  and  video-based  learning  for  fostering  learner autonomy,  pronunciation  accuracy,  and  active  engagement  in language  production. Emphasis is placed on integrated skill development, where listening supports speaking and vice versa, through reflective, feedback-informed pedagogy.Overall, the article concludes  that  a  balanced,  research-informed  approach  that  combines  theoretical foundations  with  engaging,  authentic  materials  is  key  to  advancing  learners’  oral communication abilities in English.